Pathophysiological Significance of T-type Ca2+ Channels: Properties and Functional Roles of T-type Ca2+ Channels in Cardiac Pacemaking - Kyoichi Ono; Toshihiko Iijima (Elsevier, 2005)
Calcium channels are essential for excitation-contraction coupling and pacemaker activity in cardiac myocytes. While L-type Ca2+ channels (LCC) have been extensively studied, functional roles of T-type channels (TCC) in native cardiac myocytes are still debatable. TCC are activated at more negative membrane potentials than LCC and therefore facilitate slow diastolic depolarization in sinoatrial node cells. Recent studies showed that selective inhibition of TCC produced a marked slowing of the pacemaker rhythm, indicating that contribution of TCC to cardiac automaticity was relatively larger than what had been speculated in previous studies. To re-evaluate TCC, we measured current density and kinetics of TCC in sinoatrial node cells of various mammalian species. Current density of TCC was larger in mice and guinea pigs than in rabbit and porcine sinoatrial node cells. Interestingly, few or no obvious TCC were recorded in porcine sinoatrial node cells. Furthermore, it was demonstrated that TCC could be enhanced by several vasoactive substances, thereby increasing spontaneous firing rate of sinoatrial node cells. TCC may, at least in part, account for different heart rates among various mammalian species. In addition, TCC might be involved in physiological and/or pathophysiological modulations of the heart rate. Keywords:: T-type Ca2+ channel, sinoatrial node, cardiac automaticity, pacemaker activity